Green high-performance concrete and preparation method thereof

The green high-performance concrete prepared by using specific formulas and preparation methods in concrete solves the strength and durability problems caused by uneven moisture evaporation, and significantly improves the performance and service life of concrete.

CN119822709AActive Publication Date: 2025-04-15中交一航局城市交通工程有限公司 +3
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510092238.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-21
Publication Date
2025-04-15
Estimated Expiration
2045-01-21

AI Technical Summary

Technical Problem

Existing concrete faces the problem of uneven moisture evaporation during hardening, which leads to the formation of fine pores, weakens its strength and durability, and affects the stability of long-term use.

Method used

A green high-performance concrete formula, including specific proportions of cement, mineral powder, silica fume, fly ash, sand, stone, water reducer and retarder, is prepared by the reaction of polyether polyol, hexamethylene diisocyanate and organic base, and the water reducer is prepared by the reaction of end-group olefin polyether, hydrogen peroxide and ferrous sulfate.

Benefits of technology

It significantly improves the slump, expansion, compressive strength and maximum water pressure of concrete, reduces the cracking of concrete, improves the anti-seepage performance of cement, and extends the service life of building structures.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005251902490000061
    Figure BDA0005251902490000061
Patent Text Reader

Abstract

The invention belongs to the technical field of concrete, and particularly relates to green high-performance concrete and a preparation method thereof. The invention relates to green high-performance concrete, which is prepared from 360 to 390 parts of total adhesive material, 1650 to 1800 parts of aggregate, 120 to 140 parts of water, 7.0 to 7.8 parts of water reducing agent and 4 to 6 parts of retarder, the total rubber material comprises the following components in parts by weight: 250-280 parts of cement, 52-60 parts of mineral powder, 10-15 parts of silica fume and 35-40 parts of fly ash; the aggregate is prepared from the following components in parts by weight: 730 to 800 parts of sand and 930 to 1010 parts of stone; the preparation method of the retarder comprises the following steps: reacting polyether polyol, hexamethylene diisocyanate and organic alkali 1 for 12-24 hours to obtain a mixed system, adding lignin and organic alkali 2 into the mixed system, reacting for 18-48 hours, and treating to obtain the retarder. The invention provides a new method for preparing the water reducing agent, the prepared water reducing agent and retarder are applied to concrete, the workability (slump and expansion), compressive strength and impervious maximum water pressure of the concrete are improved respectively, and the effect generated by the synergistic effect is better.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of concrete, and in particular relates to green high-performance concrete and a preparation method thereof. Background Art

[0002] In recent years, high-performance concrete, as a relatively new concrete technology, is developing rapidly and being applied to many practical engineering projects. High-performance concrete is considered to be the most comprehensive concrete in the world due to its many excellent properties such as high durability, high workability, high strength and high volume stability. It has been adopted in many important projects, especially in bridges, high-rise buildings, and seaport buildings. High-performance concrete has excellent properties that ordinary concrete cannot match. The research on high-performance concrete is one of the hottest topics in the civil engineering field today. If high-performance concrete is combined with environmental protection, ecological protection and sustainable development, it becomes green high-performance concrete.

[0003] Green high-performance concrete refers to a new type of concrete material made from recyclable materials, renewable energy and low-carbon technology, with the advantages of high strength, good durability and low carbon emissions. Among them, green means that this kind of concrete consumes less natural resources and carbon emissions during production and use, has less impact on the natural environment, and meets the requirements of sustainable development; high performance means that this kind of concrete has higher strength, durability and other mechanical properties, which can improve the safety of building structures and extend the service life of buildings. In the process of preparing green high-performance concrete, construction workers usually use a certain proportion of fly ash, silica fume, quartz powder and other industrial waste slag to replace traditional cement clinker to improve the strength and durability of green high-performance concrete and meet strict engineering construction requirements.

[0004] The performance of concrete is deeply affected by the characteristics of aggregates. Aggregates, as its main component (accounting for more than 60%), not only bear loads and resist erosion, but also significantly affect the stability of concrete. Studies have found that the size of aggregates is directly related to key indicators such as the initial slump, slump retention and slump loss of concrete. In addition, soil contamination on the surface of aggregates will weaken the bond between aggregates and cement, forming weak strength areas, reducing the overall strength, and damaging the concrete's anti-carbonation ability and weather resistance. At the same time, soil agglomeration may also cause local strength reduction, posing a safety hazard.

[0005] In order to optimize the performance of concrete, water reducers are widely used as an important additive to improve the performance of fresh concrete and hardened concrete. Although water reducers are known for their small dosage and significant effects, their preparation process is complex and energy-intensive. Energy conservation and emission reduction are particularly important in the energy-intensive field of the building materials industry.

[0006] Concrete faces the problem of uneven water evaporation during the hardening process. Slow and uneven water evaporation leads to the formation of a large number of tiny pores, which has an adverse effect on the strength of concrete. In actual projects such as road paving, the joint gaps caused by multiple parallel paving and the tiny cracks generated during the concrete hardening process will further weaken the strength and durability of concrete and affect its long-term stability. In view of these problems, there is an urgent need to innovate and develop a green high-performance concrete to improve the quality and efficiency of concrete repair and promote progress in the field of building materials. Summary of the invention

[0007] One of the purposes of the present invention is to provide a green high-performance concrete which can significantly improve concrete workability (slump, expansion), compressive strength and maximum water pressure resistance.

[0008] To achieve one of the purposes of the present invention, the technical solution adopted by the present invention is:

[0009] A green high-performance concrete, comprising 360-390 parts of total adhesive, 1650-1800 parts of aggregate, 120-140 parts of water, 7.0-7.8 parts of water reducer, and 4-6 parts of retarder; the total adhesive comprises the following components: 250-280 parts of cement, 52-60 parts of mineral powder, 10-15 parts of silica fume, and 35-40 parts of fly ash; the aggregate comprises the following components: 730-800 parts of sand, and 930-1010 parts of stone; the preparation method of the retarder comprises the following steps: reacting polyether polyol, hexamethylene diisocyanate, and organic base 1 for 12-24 hours to obtain a mixed system, adding lignin and organic base 2 to the mixed system for reaction for 18-48 hours, and then treating to obtain the retarder.

[0010] Furthermore, the mass ratio of the polyether polyol, hexamethylene diisocyanate and organic base 1 is 400:(150-165):(120-150); the lignin and organic base 2 are added to the mixed system in a mass ratio of 1:(0.5-0.7).

[0011] Furthermore, the mass ratio of the organic base 1 to the organic base 2 is 1:(1.2-1.4); the organic base 1 and the organic base 2 are one of triethylamine and pyridine.

[0012] Furthermore, the preparation method of the water reducing agent comprises the following steps:

[0013] (1) taking terminal olefin polyether, 30% hydrogen peroxide, ferrous sulfate, and acrylic acid and placing them in water to obtain liquid A; taking acrylic acid and N-hydroxymethyl acrylamide and placing them in water to obtain liquid B; taking methacryloyloxyethyl trimethyl ammonium chloride, vitamin C, and mercaptopropionic acid and placing them in water to obtain liquid C; adding the liquid B and liquid C to liquid A respectively, reacting at 35 to 50° C. for 60 to 90 minutes, and treating to obtain intermediate 1;

[0014] (2) reacting the intermediate 1, cellulose, N,N,N',N'-tetramethylazodicarbonamide and triphenylphosphine at 60-90° C. for 16-24 hours, and treating to obtain a water reducing agent.

[0015] Furthermore, the amount ratio of the terminal olefin polyether, 30% hydrogen peroxide, ferrous sulfate and acrylic acid in the liquid A is 180g: (3.5-5)mL: (0.5-0.8)g: (3-5)g.

[0016] Furthermore, the mass ratio of acrylic acid to N-hydroxymethyl acrylamide in the liquid B is 1:(0.15-0.21).

[0017] Furthermore, the mass ratio of methacryloyloxyethyltrimethylammonium chloride, vitamin C and mercaptopropionic acid in the C liquid is 1: (0.12-0.17): (0.45-0.5).

[0018] Furthermore, the terminal olefin polyether is one of isoprene polyoxyethylene ether and 4-hydroxybutyl vinyl polyoxyethylene ether.

[0019] Furthermore, the green high-performance concrete includes 361 to 389 parts of total adhesive, 1670 to 1801 parts of aggregate, 130 to 140 parts of water, 7.2 to 7.8 parts of water reducer, and 4 to 6 parts of retarder; the total adhesive includes the following components: 260 to 280 parts of cement, 54 to 58 parts of mineral powder, 10 to 12 parts of silica fume, and 36 to 39 parts of fly ash; the aggregate includes the following components: 735 to 791 parts of sand and 935 to 1010 parts of stone.

[0020] Furthermore, the fineness modulus of the sand is 2.4 to 3.0, and the maximum particle size of the stone is preferably 25 mm.

[0021] A second object of the present invention is to provide a method for preparing green high-performance concrete.

[0022] To achieve the second purpose of the present invention, the technical solution adopted by the present invention is:

[0023] The total adhesive, aggregate, water, water reducing agent and retarder are mixed and stirred to obtain green high performance concrete.

[0024] Compared with the prior art, the present invention has the following beneficial effects:

[0025] 1. Due to the uneven surface of lignin fiber, lignin fiber has a stronger bonding force with cement or aggregate, thereby reducing the cracking of concrete. Lignocellulose has a strong cross-linking and mending function. It is grafted with polyethylene glycol to prepare a retarder, which can lock water in it to retain water and slow down the setting, further increasing the bonding force between lignin fiber and cement or aggregate, thereby further reducing the cracking of concrete and improving the cement impermeability. After silica fume is added to concrete, on the one hand, silica fume reacts with Ca(OH)2 generated during the hydration process of cement under the alkaline excitation in concrete to generate CSH gel and calcium silicate hydrate, making the concrete more compact. Adding fly ash and mineral ash to concrete can reduce the hydration heat due to the reduction of cement dosage, thereby reducing the possibility of concrete cracks. The addition of fly ash increases the volume of concrete slurry. A large amount of slurry fills the pores between aggregates, wraps and lubricates aggregate particles, so that the concrete mixture has better cohesion and plasticity, and maintains the good dispersion properties of cement.

[0026] 2. The surface of cellulose is rich in hydroxyl groups. The cellulose is esterified with part of the carboxylic acid of the polycarboxylic acid water-reducing agent to graft the cellulose onto the polycarboxylic acid water-reducing agent. The present invention proposes a new water-reducing agent method. The prepared water-reducing agent and retarder are applied to concrete to respectively improve the concrete and workability (slump, expansion), compressive strength and maximum water pressure resistance, and the synergistic effect produces a better effect. DETAILED DESCRIPTION

[0027] The technical scheme of the present invention is further described below in conjunction with specific embodiments. However, it should be understood by those skilled in the art that the following examples are only used to illustrate the present invention and should not be regarded as limiting the present invention. The specific conditions not specified in the examples are carried out according to conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used, unless otherwise specified, are conventional products obtained through commercial channels.

[0028] Example 1

[0029] A green high-performance concrete, the preparation method of which comprises the following steps:

[0030] (1) Preparation of retarder

[0031] 400 g of polyethylene glycol 400, 165 g of hexamethylene diisocyanate, and 120 g of triethylamine were added to 1 L of N, N-dimethylformamide (DMF), and the mixture was stirred for 24 h to obtain a mixed system. 200 g of lignin and 100 g of pyridine were then added to the mixed system, and the mixture was stirred for 48 h. The reaction solution was filtered and dried to obtain a retarder.

[0032] (2) Preparation of retarder

[0033] 180 g of isoprenyl polyoxyethylene ether (TEPG-2400) was added to 200 mL of water, and after it was dissolved, 4 mL of 30% hydrogen peroxide, 0.5 g of ferrous sulfate and 5 g of acrylic acid were added to obtain liquid A; 13 g of acrylic acid and 2 g of N-hydroxymethyl acrylamide were placed in 15 mL of deionized water to obtain liquid B; 3 g of methacryloyloxyethyl trimethylammonium chloride, 0.4 g of vitamin C and 1.5 g of mercaptopropionic acid were placed in 40 mL of deionized water to obtain liquid C; liquid C and liquid B were simultaneously added dropwise to liquid A. After the addition was completed, the reaction solution was placed at 40° C. for reaction for 75 min, and then a 30% aqueous sodium hydroxide solution was added to neutralize the reaction solution to pH=5.55 to obtain intermediate 1.

[0034] 400 g of intermediate 1, 20 g of cellulose, 12N,N,N',N'-tetramethylazodicarbonamide and 22 g of triphenylphosphine were reacted in 500 mL of N,N-dimethylformamide (DMF) at 90° C. for 16 h, filtered and prepared into a 40% aqueous solution to obtain a water reducer.

[0035] (3) Preparation of concrete

[0036] 260 parts of cement, 54 parts of mineral powder, 11 parts of silica fume, 36 parts of fly ash, 735 parts of sand, 935 parts of stone, 130 parts of water, 7.22 parts of water reducer and 4 parts of retarder were weighed according to the formula and stirred for 3 minutes to obtain green high performance concrete.

[0037] Example 2

[0038] A green high-performance concrete, the preparation method of which comprises the following steps:

[0039] (1) Preparation of retarder

[0040] 400 g of polypropylene glycol 400, 150 g of hexamethylene diisocyanate, and 150 g of pyridine were added to 700 mL of N,N-dimethylformamide (DMF) and stirred for reaction for 36 hours to obtain a mixed system. Then, 180 g of lignin and 110 g of triethylamine were added to the mixed system and stirred for reaction for 60 hours. The reaction solution was filtered and dried to obtain a retarder.

[0041] (2) Preparation of retarder

[0042] 180 g of 4-hydroxybutyl vinyl polyoxyethylene ether (VPEG-2400) was added to 200 mL of water, and after being dissolved, 5 mL of 30% hydrogen peroxide, 0.8 g of ferrous sulfate and 4 g of acrylic acid were added to obtain liquid A; 14 g of acrylic acid and 3 g of N-hydroxymethyl acrylamide were placed in 25 mL of deionized water to obtain liquid B; 4 g of methacryloyloxyethyl trimethylammonium chloride, 0.5 g of vitamin C and 1.8 g of mercaptopropionic acid were placed in 50 mL of deionized water to obtain liquid C; liquid C and liquid B were simultaneously added dropwise to liquid A, and after the addition was completed, the reaction solution was placed at 35° C. for reaction for 90 min, and then a 30% sodium hydroxide aqueous solution was added to neutralize the reaction solution to pH=6 to obtain intermediate 1.

[0043] 400 g of solid intermediate 1, 15 g of cellulose, 15 g of N,N,N',N'-tetramethylazodicarbonamide and 25 g of triphenylphosphine were reacted in 700 mL of N,N-dimethylformamide (DMF) at 60° C. for 24 h, filtered and prepared into a 35% aqueous solution to obtain a water reducer.

[0044] (3) Preparation of concrete

[0045] 270 parts of cement, 56 parts of mineral powder, 11 parts of silica fume, 38 parts of fly ash, 763 parts of sand, 971 parts of stone, 135 parts of water, 7.50 parts of water reducer and 5 parts of retarder were weighed and mixed according to the formula to obtain green high performance concrete.

[0046] Example 3

[0047] A green high-performance concrete, the preparation method of which comprises the following steps:

[0048] (1) Preparation of retarder

[0049] 400 g of polyethylene glycol 400, 160 g of hexamethylene diisocyanate, and 135 g of triethylamine were added to 800 mL of N,N-dimethylformamide (DMF) and stirred for reaction for 24 h to obtain a mixed system. Then, 150 g of lignin and 105 g of triethylamine were added to the mixed system and stirred for reaction for 72 h. The reaction solution was filtered and dried to obtain a retarder.

[0050] (2) Preparation of retarder

[0051] 180 g of isoprenyl polyoxyethylene ether (TEPG-2400) was added to 200 mL of water, and after being dissolved, 3.5 mL of 30% hydrogen peroxide, 0.7 g of ferrous sulfate and 3 g of acrylic acid were added to obtain liquid A; 15 g of acrylic acid and 2.5 g of N-hydroxymethyl acrylamide were placed in 20 mL of deionized water to obtain liquid B; 3.5 g of methacryloyloxyethyl trimethylammonium chloride, 0.6 g of vitamin C and 1.6 g of mercaptopropionic acid were placed in 45 mL of deionized water to obtain liquid C; liquid C and liquid B were simultaneously added dropwise to liquid A, and after the addition was completed, the reaction solution was placed at 50° C. for reaction for 60 min, and then a 30% sodium hydroxide aqueous solution was added to neutralize the reaction solution to pH=6.5 to obtain intermediate 1.

[0052] 400 g of solid intermediate 1, 18 g of cellulose, 18 N, N, N', N'-tetramethylazodicarbonamide and 27 g of triphenylphosphine were reacted in 500 mL of N, N-dimethylformamide (DMF) at 70° C. for 18 h, filtered and prepared into a 30% aqueous solution to obtain a water reducer.

[0053] (3) Preparation of concrete

[0054] Weigh 280 parts of cement, 58 parts of mineral powder, 12 parts of silica fume, 39 parts of fly ash, 791 parts of sand, 1010 parts of stone, 140 parts of water, 7.78 parts of water reducer and 6 parts of retarder according to the formula and mix them evenly to obtain green high-performance concrete.

[0055] Comparative Example 1

[0056] A green concrete, which differs from Example 1 in that step (1) is omitted and the retarder in step (3) is replaced by an equal amount of lignin.

[0057] Comparative Example 2

[0058] A green concrete, which differs from Example 1 in that step (2) is omitted and the water reducing agent in step (3) is replaced by an equal amount of intermediate 1.

[0059] Comparative Example 3

[0060] A green concrete, which differs from Example 1 in that: steps (1) and (2) are omitted, the water reducer in step (3) is replaced by an equal amount of intermediate 1, the retarder in step (3) is omitted, and cellulose in an amount equal to the water reducer and lignin in an amount equal to the retarder are added thereto.

[0061] Comparative Example 4

[0062] A green concrete, which differs from Example 1 in that: steps (1) and (2) are omitted, the water reducing agent in step (3) is replaced by an equal amount of intermediate 1, and the retarder in step (3) is omitted.

[0063] Test example

[0064] The samples prepared in Examples 1 to 3 and Comparative Examples 1 to 3 were subjected to performance tests: concrete specimens of each embodiment and comparative example were prepared according to the test requirements, the concrete compression specimen had a size of 100 mm × 100 mm × 100 mm, the flexural specimen had a size of 150 mm × 150 mm × 550 mm, the impermeability specimen had a size of 150 mm × φ175 mm × φ185 mm, and the electric flux specimen had a size of a cylinder with a diameter of (100 ± 1) mm and a height of (50 ± 2) mm. After each specimen was cured to the specified age according to the standard, relevant tests were carried out. The slump of concrete was tested according to GB50164-92 "Concrete Quality Control Standard" to evaluate the fluidity of concrete. The compressive strength test was carried out according to the "Standard for Test Methods for Mechanical Properties of Ordinary Concrete" GB / T50081-2019. According to the "Standard for Test Methods for Long-term Performance and Durability of Ordinary Concrete" GB / T50082-2009, the impermeability test was carried out using an impermeability meter, and the chloride ion penetration test was carried out using the electric flux method. The comparative test results of each embodiment and comparative example are shown in Table 1.

[0065] Table 1

[0066]

[0067] As shown in Table 1, compared with the comparative example 4 in which only the intermediate 1-polycarboxylate water reducer is added, the comparative example 1 adding water reducer and lignin improves the concrete workability (slump, expansion), compressive strength and maximum water pressure of impermeability; the comparative example 2 adding the intermediate 1-polycarboxylate water reducer and retarder improves the concrete workability (slump, expansion), compressive strength and maximum water pressure of impermeability; the comparative example 3 adding lignin, intermediate 1-polycarboxylate water reducer, cellulose improves the compressive strength and maximum water pressure of impermeability, and reduces the workability (slump, expansion); however, compared with the comparative example 4, the electric flux (56 days) of the concrete of Examples 1 to 3 is increased by 7 to 9C. The workability (slump, expansion), compressive strength and maximum water pressure of impermeability of Examples 1 to 3 are significantly better than those of Comparative Examples 1 to 4, which shows that the water reducer and retarder can improve the concrete workability (slump, expansion), compressive strength and maximum water pressure of impermeability separately, and the synergistic effect is better.

[0068] The above are only preferred embodiments of the present invention, and are not limited to the above examples. For those skilled in the art, various changes and variations are possible under the principle of the present invention. Any modifications and improvements made should be considered within the scope of protection of the present invention.

Claims

1. A green high performance concrete, characterized in that: The green high-performance concrete includes 360-390 parts of total adhesive, 1650-1800 parts of aggregate, 120-140 parts of water, 7.0-7.8 parts of water reducer, and 4-6 parts of retarder; the total adhesive includes the following components: 250-280 parts of cement, 52-60 parts of mineral powder, 10-15 parts of silica fume, and 35-40 parts of fly ash; the aggregate includes the following components: 730-800 parts of sand and 930-1010 parts of stone; the preparation method of the retarder includes the following steps: reacting polyether polyol, hexamethylene diisocyanate, and organic base 1 for 12-24 hours to obtain a mixed system, adding lignin and organic base 2 to the mixed system to react for 18-48 hours, and then treating to obtain the retarder.

2. The green high performance concrete according to claim 1, characterized in that: The mass ratio of the polyether polyol, hexamethylene diisocyanate and organic base 1 is 400:(150-165):(120-150); the lignin and organic base 2 are added to the mixed system at a mass ratio of 1:(0.5-0.7).

3. The green high performance concrete according to claim 1, characterized in that: The mass ratio of the organic base 1 to the organic base 2 is 1:(1.2-1.4); the organic base 1 and the organic base 2 are one of triethylamine and pyridine.

4. The green high performance concrete according to claim 1, characterized in that: The preparation method of the water reducing agent comprises the following steps: (1) taking terminal olefin polyether, 30% hydrogen peroxide, ferrous sulfate, and acrylic acid and placing them in water to obtain liquid A; taking acrylic acid and N-hydroxymethyl acrylamide and placing them in water to obtain liquid B; taking methacryloyloxyethyl trimethyl ammonium chloride, vitamin C, and mercaptopropionic acid and placing them in water to obtain liquid C; adding the liquid B and liquid C to liquid A respectively, reacting at 35 to 50° C. for 60 to 90 minutes, and treating to obtain intermediate 1; (2) reacting the intermediate 1, cellulose, N,N,N',N'-tetramethylazodicarbonamide and triphenylphosphine at 60-90° C. for 16-24 hours, and treating to obtain a water reducing agent.

5. The green high performance concrete according to claim 4, characterized in that: The amount ratio of the terminal olefin polyether, 30% hydrogen peroxide, ferrous sulfate and acrylic acid in the liquid A is 180g: (3.5-5)mL: (0.5-0.8)g: (3-5)g.

6. The green high performance concrete according to claim 4, characterized in that: The mass ratio of acrylic acid to N-hydroxymethyl acrylamide in the liquid B is 1:(0.15-0.21).

7. The green high performance concrete according to claim 4, characterized in that: The mass ratio of methacryloyloxyethyltrimethylammonium chloride, vitamin C and mercaptopropionic acid in the C liquid is 1: (0.12-0.17): (0.45-0.5).

8. The green high performance concrete according to claim 4, characterized in that: The terminal olefin polyether is one of isoprene polyoxyethylene ether and 4-hydroxybutyl vinyl polyoxyethylene ether.

9. The green high performance concrete according to claim 1, characterized in that: The green high-performance concrete includes 361-389 parts of total adhesive, 1670-1801 parts of aggregate, 130-140 parts of water, 7.2-7.8 parts of water reducer, and 4-6 parts of retarder; the total adhesive includes the following components: 260-280 parts of cement, 54-58 parts of mineral powder, 10-12 parts of silica fume, and 36-39 parts of fly ash; the aggregate includes the following components: 735-791 parts of sand and 935-1010 parts of stone.

10. The method for preparing green high performance concrete according to claim 1, characterized in that: The following steps are involved: The total adhesive, aggregate, water, water reducing agent and retarder are mixed and stirred to obtain green high performance concrete.

Citation Information

Patent Citations

  • Green high-performance concrete

    CN106630901A

  • Self-curing polycarboxylic type water reducer and preparation method thereof

    CN107057003A

  • Preparation method of underwater super-retarded concrete

    CN118344089A